2017
DOI: 10.1111/jomf.12413
|View full text |Cite
|
Sign up to set email alerts
|

Does Educational Similarity Drive Parental Support?

Abstract: This article tests competing mechanisms explaining linkages between parent–child educational similarity and parental advice and interest to adult children, asking whether mechanisms differ for mothers and fathers. Educational similarities might provide common ground whereas educational dissimilarity affects parents' authority to dispense advice. Using ordered logistic regression with data from the Netherlands Kinship Panel Study (N = 2,444) parental advice and interest are modeled separately for mothers and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Perhaps paternal differential treatment, too, is more strongly influenced by physical than personality similarity (Heijkoop et al, 2009). Second, research showed that fathers show more interest in adult children who are similar in educational attainment (Ory et al, 2017). Future research might thus examine the effect of different types of similarity on paternal differential treatment, such as physical or educational similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps paternal differential treatment, too, is more strongly influenced by physical than personality similarity (Heijkoop et al, 2009). Second, research showed that fathers show more interest in adult children who are similar in educational attainment (Ory et al, 2017). Future research might thus examine the effect of different types of similarity on paternal differential treatment, such as physical or educational similarity.…”
Section: Discussionmentioning
confidence: 99%